2015
DOI: 10.4137/cmc.s22022
|View full text |Cite
|
Sign up to set email alerts
|

An International Observational Prospective Survey Assessing the Control of Atrial Fibrillation in Asia-Pacific: Results of the Record-AFAP Registry

Abstract: A prospective 1-year observational survey was designed to assess the management and control of atrial fibrillation (AF) in eight countries within the Asia-Pacific region. Patients (N = 2,604) with recently diagnosed AF or a history of AF ≤1 year were included. Clinicians chose the treatment strategy (rhythm or rate control) according to their standard practice and medical discretion. The primary endpoint was therapeutic success. At baseline, rhythm- and rate-control strategies were applied to 35.7% and 64.3% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…(26) Consistent with this, in both Australia and Singapore, our study included a higher percentage of males and hypertension was the most common co-morbidity. The most common concurrent treatment at both sites was with betablockers which is also consistent with Amerena et al (14) who concluded that clinicians in the Asia-Pacific region prefer rate-control strategies. However there were several differences between the two populations.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…(26) Consistent with this, in both Australia and Singapore, our study included a higher percentage of males and hypertension was the most common co-morbidity. The most common concurrent treatment at both sites was with betablockers which is also consistent with Amerena et al (14) who concluded that clinicians in the Asia-Pacific region prefer rate-control strategies. However there were several differences between the two populations.…”
Section: Resultssupporting
confidence: 84%
“…Amerena et al (14) found significant regional differences in treatment strategies and clinical cardiovascular outcomes in AF patients across Asia-Pacific countries. Chen et al (15) reported more than 70% of physicians in Australia and Singapore prescribe oral anticoagulants for stroke prevention but found suboptimal warfarin control to be a larger problem in Asia than other regions.…”
Section: Introductionmentioning
confidence: 99%